Simultaneous effects of pressure and magnetic field on intersubband optical transitions in Pöschl–Teller quantum well - Hakimyfard, Alireza; Barseghyan, M.G.; Kirakosyan, A.A. (Physica. E, Low-dimensional systems & nanostructures, 2009)
The simultaneous effects of hydrostatic pressure and magnetic field applied along the quantization direction on intersubband optical transitions in Pöschl–Teller quantum well are investigated. The expression of the absorption coefficient and some selection rules are obtained. The dependences of the absorption coefficient on magnetic field induction and incident photon energy for different values of pressure and parameters of quantum well are obtained as well.